2000
DOI: 10.1002/1521-4141(200010)30:10<2991::aid-immu2991>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Induction of the IL-10 gene via the Fas receptor in monocytes - an anti-inflammatory mechanism in the absence of apoptosis

Abstract: Death receptors play an important role in controlling cell numbers and immune responses. In contrast to TNF receptors, little is known about non‐apoptosis functions of the Fas receptor (CD95, APO‐1). Here we demonstrate that Fas receptor engagement results in the induction of the IL‐10 gene in monocytes, but not in lymphocytes or dendritic cells. In contrast, TNF‐α stimulated IL‐10 production in dendritic cells but not monocytes. Fas receptor‐mediated transcriptional activation of the IL‐10 gene was followed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 29 publications
1
17
0
Order By: Relevance
“…It has also been demonstrated that Fas signaling in macrophages induces IL-10 gene expression. 36 We have recently reported that natural killer T cells in the liver express Fas-ligand directly through toll-like receptors induced by gram-negative bacteria such as Salmonella choleraesuis and E. coli. 37,38 Taken together, it also seems likely that Fas-expressing Kupffer cells in BDL mice are susceptible to signals via Fas-ligand expressed on natural killer T cells after E. coli infection and predominantly produce IL-10.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been demonstrated that Fas signaling in macrophages induces IL-10 gene expression. 36 We have recently reported that natural killer T cells in the liver express Fas-ligand directly through toll-like receptors induced by gram-negative bacteria such as Salmonella choleraesuis and E. coli. 37,38 Taken together, it also seems likely that Fas-expressing Kupffer cells in BDL mice are susceptible to signals via Fas-ligand expressed on natural killer T cells after E. coli infection and predominantly produce IL-10.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated that the FasL can transduce signals via the Fas receptor using nonapoptotic pathways in monocytes (33), dendritic cells (34), and T cells (35). In addition, studies have shown that CD4 ϩ T cells and CD8 ϩ T cells exhibit different sensitivities to Fasmediated apoptosis (36,37).…”
Section: Discussionmentioning
confidence: 99%
“…The finding that Fas cross-linking induces the expression of IL-10 in murine lymphoid cells (10,11) prompted us to investigate whether a similar pathway operates in Jurkat cells. The transcription of IL-10 in Jurkat cells was induced by CH-11 in a dosedependent manner (Fig.…”
Section: Enhanced Transcription Of the Il-10 Gene In Jurkat Cells Is mentioning
confidence: 99%
“…Fas-L costimulates the proliferation of CD8 ϩ T cells and resting T lymphocytes by augmenting IL-2 production (8,9). Fas-mediated transcriptional activation of the IL-10 gene in monocytes was followed by the release of large amounts of cytokines and occurred in the absence of apoptosis (10). Moreover, apoptosis in lymphoid cells upon Fas activation led to rapid production of IL-10, which is probably responsible for the induction of immune deviation during Ag presentation (11).…”
mentioning
confidence: 99%